2010
DOI: 10.1542/peds.2010-0222
|View full text |Cite
|
Sign up to set email alerts
|

Parental BMI and Childhood Undernutrition in India: An Assessment of Intrauterine Influence

Abstract: Similarity in the association between paternal/maternal BMI and childhood undernutrition suggests that intergenerational associations in nutritional status are not driven by maternal intrauterine influences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
48
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 42 publications
(47 reference statements)
16
48
1
Order By: Relevance
“…Rather, short stature reflects the cumulative net impact of nutrition and, therefore, the roles of disease and more distal environmental conditions, such as socioeconomic status, on height over time and across generations. That the two regions of the world with the lowest average adult heights are also the regions with the greatest prevalence of undernourishment (sub-Saharan Africa) and the greatest number of undernourished people (Southeast Asia) 219 supports this claim. Moreover, at the individual level, the relative roles of net nutrition and genetics appear to differ between the growth periods: the impact of nutrition (and other environmental factors) may be relatively stronger during the first period, while the genetic component may be relatively stronger during the second period.…”
Section: Discussionmentioning
confidence: 87%
“…Rather, short stature reflects the cumulative net impact of nutrition and, therefore, the roles of disease and more distal environmental conditions, such as socioeconomic status, on height over time and across generations. That the two regions of the world with the lowest average adult heights are also the regions with the greatest prevalence of undernourishment (sub-Saharan Africa) and the greatest number of undernourished people (Southeast Asia) 219 supports this claim. Moreover, at the individual level, the relative roles of net nutrition and genetics appear to differ between the growth periods: the impact of nutrition (and other environmental factors) may be relatively stronger during the first period, while the genetic component may be relatively stronger during the second period.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that women with secondary education are better informed about optimal child care practices [8], have better practices in terms of hygiene [27,28], feeding [18] and childcare during illness [18,21,22], have a greater ability to use the health system [29], are more empowered to make decisions [28] and are more likely to have financial resources to care for and feed children [18]. There has been a slight increase in the percentage of women who have completed secondary education in Rwanda, from 1.2 % in 2005 [30] to 2.8 % in 2010 [10], and we hypothesize that further gains in women's education may translate into improved child nutrition outcomes [7,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting the National Family Health Survey (NFHS Round 3) findings of [2005][2006] with that of an earlier survey, the study even highlighted that more children and women in India had anemia than in 1998 and more children showed wasting through malnutrition. A different team of researchers, who also used the NFHS 2005-2006 dataset, concluded that intergenerational mechanisms linking under-nutrition across subsequent generations seemed to depend particularly on continuity of adversity, rather than being determined by intrauterine biological processes [3]. Against this background, the current study was situated in the Sundarbans area of the district of south-24 Parganas in West Bengal, India.…”
Section: Introductionmentioning
confidence: 94%